テイイド オヨビ コウイド ニオケル Pcガタ チジキ ミャクドウ ノ トクセイ ノ タイヒ 1 d. ジキケンナイ ノ ULF ハドウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 桑島, 正幸; クワシマ, マサユキ; 外谷, 健; トヤ, タケシ; 河村, 〓; カワムラ, マコト; KUWASHIMA, Masayuki; TOYA, Takeshi; KAWAMURA, Makoto (1980)
P(論文) 1977年2月から1978年1月の期間,中低緯度の観測点女満別と極光帯に位置する昭和基地で得られたPc 1を対象にして,その特性の対比を目的とした解析を行った.その結果両者の間には,出現頻度の日変化および季節変化,中心周期,地磁気活(Dst, Kp)等で大きな相違がみられる.このことは両者の発生領域が異なることを示していると考えられる. Statistical features of Pc 1 pulsations were studied on the basis of data obtained at a low-latitude station, Memambetsu in Japan and at a high-latitude station, Syowa Station in Antarctica, for the period of February 1977 to January 1978. The low-latitude Pc 1 shows distinct difference from the high-latitude one in diurnal and seasonal variations of frequency of occurrence, mean and repetition periods and dependencies on general geomagnetic activity (Dst and Kp). A source region associated with the low-latitude Pc 1 may be located further inside in the magnetosphere than that associated with the high-latitude one departmental bulletin paper